2022
DOI: 10.1007/s13201-022-01837-7
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of nano zero-valent aluminum for one-step removal of methylene blue from aqueous solutions: cost analysis for scaling-up and artificial intelligence

Abstract: Methylene blue (MB) is a heterocyclic aromatic dye that is difficult to biodegrade due to its complex chemical structure. In this study, chemically prepared nano zero-valent aluminum (nZVAl) was investigated for the first time for one-step removal of MB from aqueous solutions under different experimental factors (pH, dosage, time, MB concentration, stirring rate, temperature, detergents, and ionic strength). The prepared nZVAl material was characterized using XRD, TEM, SEM, EDS, and FTIR. Results indicated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 106 publications
0
5
0
Order By: Relevance
“…In contrast, the Dubinin-Radushkevich (D-R) model was employed to determine the apparent free energy of adsorption (E), which is commonly used to differentiate between physical and chemical adsorption. The adsorption energy calculated from the D-R isotherms for MB on NGC indicated physical adsorption [62][63][64], with Q m values decreasing as temperature increased, suggesting an exothermic adsorption process [65].…”
Section: Isotherm Study Of Adsorptionmentioning
confidence: 99%
“…In contrast, the Dubinin-Radushkevich (D-R) model was employed to determine the apparent free energy of adsorption (E), which is commonly used to differentiate between physical and chemical adsorption. The adsorption energy calculated from the D-R isotherms for MB on NGC indicated physical adsorption [62][63][64], with Q m values decreasing as temperature increased, suggesting an exothermic adsorption process [65].…”
Section: Isotherm Study Of Adsorptionmentioning
confidence: 99%
“…Nano-scale zero-valent aluminum (nZVAl) particles were synthesized via the sodium borohydride reduction method (NaBH 4 , Winlab Co., UK) [21,40]. Briefly, aluminum sulfate (Al 2 (SO 4 ) 3 •18H 2 O, Loba Chemie, India) was dissolved in distilled water and the mixture was aggressively agitated at 500 rpm by a magnetic bar.…”
Section: Synthesis Of Adsorbentmentioning
confidence: 99%
“…The nZVAl material has been evidenced to be effective in removing non-biodegradable pollutants by generating hydroxyl radicals and sulfate in the aqueous medium [20]. Many researchers have reported that nZVAl was effective in removing phenol, nitrobenzene, perchlorate, chromium(VI), chloride, nitrate, dye compounds, bisphenol A, and hexabromocyclododecane from contaminated water [20][21][22]. Nanoscale ZVAl is an active and stable metal with a large surface area, having a wide range of versatility and flexibility for in-situ applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The elimination of toxic organic pollutants such as heptachlor epoxide were investigated utilizing several approaches, including degradation, adsorption, electrocoagulation, enzymes, bacteria, and nanotechnologies [13][14][15][16]. Nano zero-valet metals such as iron has been widely employed in wastewater treatment by adsorption and degradation process, especially for pesticide removal [17][18][19]. The utilization of nano zero-valent iron is a highly promising technology for eliminating not just organochlorine pesticides, but also a wide range of other micropollutants [20,21].…”
Section: Introductionmentioning
confidence: 99%